Ecological practical wisdom: common stances across design and planning. Issue 1 (26th April 2019) - Grose, Margaret J; Wang, Yuncai; Cheng, Yuning; Yan, Wentao; Forester, John; Steiner, Frederick
Abstract: This article is an overview of six lectures given at the Inaugural Tongji Advanced Lecture Series on Frontiers in Ecophronetic Practice Research . Lectures focused on the problems and current state of ecophronetic practice (i.e., use of practical wisdom) and included discussion of place-dependent actions, global ideas into local practice, the integration of systems, working with communities and the teaching of ecophronetic practice.